Methylation-mediated silencing of EDN3 promotes cervical cancer proliferation, migration and invasion - Zhu, Peng; Li, Xiang; Liu, Yujie; Xiong, Jing; Yuan, Ding; Chen, Yan; Luo, Lili; Huang, Ju; Wang, Binbin; Nie, Quanfang; Wang, Shuli; Dang, Liying; et al. (Frontiers in Oncology, 2023)
Cervical cancer (CC) remains one of the leading causes of cancer-related deaths worldwide. However, cervical cancer is preceded by the pre-malignant cervical intraepithelial neoplasia (CIN) that can last for up to 20 years before becoming malignant. Therefore, early screening is the key to prevent the progression of cervical lesions into invasive cervical cancer and decrease the incidence. The genes, down-regulated and hypermethylated in cancers, may provide potential drug targets for cervical cancer. In our current study, using the datasets from Gene Expression Omnibus (GEO) and the Cancer Genome Atlas (TCGA) databases, we found that endothelin 3 (EDN3) was downregulated and hypermethylated in cervical squamous cell carcinoma (CSCC). The further analysis in GSE63514 (n=128) dataset and in our samples (n=221) found that the expression of EDN3 was decreased with the degree of cervical lesions. Pyrosequencing was performed to evaluate 4 CpG sites of the EDN3 promoter region in our samples (n=469). The data indicated that the methylation level of EDN3 was increased with the degree of cervical lesions. EDN3 silencing mediated by methylation can be blocked by 5-Azacytidine (5-Aza), a DNA methyltransferase 1 (DNMT1) inhibitor, treatment in cervical cancer cell lines. Ethynyldeoxyuridine (EdU) assay, would-healing assay, clone formation assay and transwell assay were conducted to investigate the biological function of EDN3 in cervical cancer cell lines. The results of these experiments confirmed that overexpression of EDN3 could inhibit the proliferation, clone formation, migration and invasion of cervical cancer cells. EDN3 may provide potential biomarker and therapeutic target for CSCC.